2003
DOI: 10.1063/1.1624639
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, deep-blue organic electrophosphorescence by guest charge trapping

Abstract: We demonstrate efficient, deep-blue organic electrophosphorescence using a charge-trapping phosphorescent guest, iridium(III) bis(4′,6′-difluorophenylpyridinato)tetrakis(1-pyrazolyl)borate (FIr6) doped in the wide-energy-gap hosts, diphenyldi(o-tolyl)silane (UGH1) and p-bis(triphenylsilyly)benzene (UGH2), where exciton formation occurs directly on the guest molecules. Charge trapping on the guest is confirmed by the dependence of the drive voltage and electroluminescence spectrum on guest concentration. Ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
423
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(438 citation statements)
references
References 15 publications
14
423
0
1
Order By: Relevance
“…Recently, Hatakeyama et al reported a new strategy to design effective deep blue triarylboron based emitters [95]. The chemical structures of boron emitters (28)(29) are given in Figure 6, while their novel design strategy is displayed in Figure 7. It is well known that efficient TADF-based OLEDs need a fluorophore with a small ∆E ST .…”
Section: Triarylborane Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hatakeyama et al reported a new strategy to design effective deep blue triarylboron based emitters [95]. The chemical structures of boron emitters (28)(29) are given in Figure 6, while their novel design strategy is displayed in Figure 7. It is well known that efficient TADF-based OLEDs need a fluorophore with a small ∆E ST .…”
Section: Triarylborane Emittersmentioning
confidence: 99%
“…The authors obtained pure blue TADF molecules by using multiple resonance effect to efficiently separate HOMO-LUMO. The first molecule (28) showed in the Figure 6 comprises a triphenylboron donor fused with two triphenylamine acceptors. The second molecule (29) is designed by increasing the length of the π-conjugated system as well as the number of electron donors.…”
Section: Triarylborane Emittersmentioning
confidence: 99%
“…[1][2][3][4] Large efforts to enable the high luminescence performance in OLEDs [5][6][7] have resulted in multilayered device architectures. On the contrary, the simple structure should have some advantages because it allows the brief fabrication of the device.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In the research stream, organic semiconductors with a wide bandgap are becoming important because triplet excitons must be confined in the phosphors. In particular, wide bandgap organic semiconducting materials are attractive as blue light-emitting phosphors [3][4][5], because the well-known energy gap between the lowest triplet excited state (T 1 ) and ground state (S 0 ) of organic materials has become much smaller than that between the lowest singlet excited state (S 1 ) and S 0 . Furthermore, since wide bandgap organic semiconducting materials are potentially applicable to ultraviolet (UV: below the wavelength of 380 nm) light emission devices, surface UV light-emitting devices, which are hardly available using other light-emitting technologies, could open another application field for organic devices.…”
mentioning
confidence: 99%